An Ethnobotanical Study of Medicinal Plants in Mersin (Turkey) - Emre, Gizem; Dogan, Ahmet; Haznedaroglu, Mehmet Zeki; Senkardes, Ismail; Ulger, Mahmut; Satiroglu, Aysen; Can Emmez, Berivan; Tugay, Osman (Frontiers in Pharmacology, 2021)
This comprehensive ethnobotanical study carried out in Mersin province, which is located in the southern part of Anatolia, east of the Mediterranean Sea, compiles details on plants used in folk medicine and ethnopharmacological information obtained through face-to-face interviews. The aim was to collect and identify plants used for therapeutic purposes by local people and to record information on traditional herbal medicine. Plant specimens were collected in numerous excursions. Additionally, informant consensus factor and use value (UV) were calculated for information gathered. This study identifies 93 plant taxa belonging to 43 families and records their usage in folk medicine; 83 taxa are wild and the remaining 10 are cultivated. The most commonly used plants belong to Lamiaceae, representing 15.0% of the total, while the Rosaceae, Malvaceae, Hypericaceae, Asteraceae and Cupressaceae families each represented another 5.4%. As a result of this investigation, we determine 189 medicinal usages of 93 taxa. The UV values indicate that the most important medicine plants are Hypericum perforatum (0.80), Cedrus libani (0.78), Quercus coccifera (0.77), Arum dioscoridis (0.76) and Juniperus drupaceae (0.74). We observed that most of the drugs are prepared using the infusion method (27.6%). As a conclusion, the study finds that traditional folk medicine usage is still common, especially among the rural population of Mersin.